2008
DOI: 10.1158/1055-9965.epi-08-0140
|View full text |Cite
|
Sign up to set email alerts
|

Methionine-Dependence Phenotype in the de novo Pathway in BRCA1 and BRCA2 Mutation Carriers with and without Breast Cancer

Abstract: Methionine-dependence phenotype (MDP) refers to the reduced ability of cells to proliferate when methionine is restricted and/or replaced by its immediate precursor homocysteine. MDP is a characteristic of human tumors in vivo, human tumor cell lines, and normal somatic tissue in some individuals. It was hypothesized that MDP is a risk factor for developing breast cancer in BRCA (BRCA1 and BRCA2) germline mutation carriers. To test the hypothesis, human peripheral blood lymphocytes of BRCA carriers with and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 45 publications
2
11
0
3
Order By: Relevance
“…Naushad et al, 2012 (plasma folate and homocysteine were measured using the Axsym folate kit and reverse phase HPLC, respectively) [30], found an association of (MTR) A2756G (OR: 4.71, 95% CI: 1.66-13.31) with breast cancer in India, Lu et al, 2010, stratifying by the menopausal status, by meta-analysis [31], suggest that the MTR A2756G polymorphism may contribute to susceptibility to breast cancer among Europeans. Beetstra et al, in 2008 worked upon 3 study groups (mean age 56.4 ±2.44 years, 47.0 ±3.12 years, and 51.0 ±2.37 years for controls) and measured plasma folate (12.4 ±0.9 nmol/l), plasma vitamin B 12 (pmol/l) was 249 ±17, and plasma homocysteine (µmol/l) was 7.9 ±0.3 [32], and found that MTR A2756G was associated with increased breast cancer risk [OR: 3.2 (p = 0.16; 95% CI: 0.76-13.9)].…”
Section: Discussionmentioning
confidence: 99%
“…Naushad et al, 2012 (plasma folate and homocysteine were measured using the Axsym folate kit and reverse phase HPLC, respectively) [30], found an association of (MTR) A2756G (OR: 4.71, 95% CI: 1.66-13.31) with breast cancer in India, Lu et al, 2010, stratifying by the menopausal status, by meta-analysis [31], suggest that the MTR A2756G polymorphism may contribute to susceptibility to breast cancer among Europeans. Beetstra et al, in 2008 worked upon 3 study groups (mean age 56.4 ±2.44 years, 47.0 ±3.12 years, and 51.0 ±2.37 years for controls) and measured plasma folate (12.4 ±0.9 nmol/l), plasma vitamin B 12 (pmol/l) was 249 ±17, and plasma homocysteine (µmol/l) was 7.9 ±0.3 [32], and found that MTR A2756G was associated with increased breast cancer risk [OR: 3.2 (p = 0.16; 95% CI: 0.76-13.9)].…”
Section: Discussionmentioning
confidence: 99%
“…In two populations, i.e., Greece (Kakkoura et al 2015) and China (He et al 2014), this polymorphism showed an inverse association with breast cancer risk while in other population, it showed a null association (Platek et al 2009;Weiwei et al 2014;He et al 2014). MTRR A66G was identified as a risk for breast cancer in a Russian population (Tao et al 2009), while it was shown to have an inverse association with Thai (Sangrajrang et al 2009;Sangrajrang et al 2010) and Australian (Beetstra et al 2008) populations. In another eight populations, MTRR A66G showed a null association (Kotsopoulos et al 2008;Burcoş et al 2010;Weiner et al 2012).…”
Section: Introductionmentioning
confidence: 98%
“…In rest of the population (N = 10), the association of this polymorphism was either borderline or null (Shrubsole et al 2004;Lee et al 2004;Inoue et al 2008;Ma et al 2009;Hosseini et al 2011;Prasad and Wilkhoo 2011;Akram et al 2012;Awwad et al 2015). MTR A2756G was investigated in ten different populations out of which it was identified as a risk factor in Iranian (Hosseini 2013) and Australian (Beetstra et al 2008) populations. In two populations, i.e., Greece (Kakkoura et al 2015) and China (He et al 2014), this polymorphism showed an inverse association with breast cancer risk while in other population, it showed a null association (Platek et al 2009;Weiwei et al 2014;He et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…У носителей аллеля G низкий уровень хромосомных аберраций совпадает с более высоким шансом на длительную продолжительность жизни [79,80]. При раке молочной железы мутация A2756G может не только стимулировать синтез метионина de novo, но и вносить вклад в формирование метио-ниновой зависимости [81].…”
Section: механизмы развития метиониновой зависимости в опухолевых клеunclassified
“…Следо-вательно, развитию метиониновой зависимости опухолевых клеток также могут способствовать на-рушения метаболизма фолатов. MTHFR с мутацией С677Т существенно увеличивал метиониновую зависимость клеток рака молочной железы [81]. Однако на культуре клеток карциносаркомы Уокера показано, что 5-MTHF не влияет на метиониновую зависимость [83].…”
Section: механизмы развития метиониновой зависимости в опухолевых клеunclassified